PENGARUH PEMBELAJARAN TERPADU MODEL WEBBED TERHADAP HASIL BELAJAR SENI BUDAYA KELAS VIII DI SMP PEMBANGUNAN LABORATORIUM UNP KOTA PADANG - Masya, Necya Khairyah; Astuti, Fuji (SENDRATASIK UNP, 2019)
Abstract This article aims to determine the effects and differences of the integrated learning of the webbed model on the learning outcomes of Grade VIII students in art and culture subjects at SMP Pembangunan Laboratorium UNP. The type of this research was quantitative research using experimental method. The objects of research were students of grade VIII, with researcher’s instruments. The techniques of data collection were conducted through learning outcomes test aspects of knowledge and skills as well as observation. Then, the data were analyzed quantitaively towards the learning outcomes by means of normality, homogeneity, and hypothesis testing. The results confimed that the use of a webbed integrated learning model in learning arts and culture created students more actively excited and easier to understand the material in learning. Meanwhile, through the results of learning arts and culture, it could be seen that the experimental class students had higher grades and were better than the control class. It indicated, in the aspect of knowledge, the average value using the integrated learning model webbed was 83.3 whereas in the control class using conventional methods, the average value of learning outcomes was 76.4. By means of the t test obtained Fcount 10.36 while Ftabel 1.67 with a significance level of 0.05. As a result, the value of Fcount > Ftabel. Thus, the hypothesis was accepted. Keywords: Integrated Learning Webbed model, Cultural Arts.